PENGARUH MASERAT LIDAH BUAYA (Aloe vera) TERHADAP KADAR KOLESTEROL DARAH MENCIT (Mus musculus) JANTAN HIPERGLIKEMIA - Lubis, Eva Anriani; Saepudin, Dr.; Soesilawati, Soesy Asiah (Formica Online, 2014)
Research on the effect of Aloe vera (Aloe vera) leaf gel macerate on blood cholesterol level of hyperglicemic mice (Mus musculus) has done. The purpose of this study was to analyze the effect of giving the Aloe vera (Aloe vera) leaf gel macerate on blood cholesterol level, so this research can be used for the basic information to develop an anti-hyperlipidemia drug by Aloe vera and this research also analyze effect the different dose of Aloe vera leaf gel macerate on blood cholesterol level in mice. An hyperglicemic condition was induced by giving 0,65 ml/100g BW alloxan to the mice intrevenaly. Complete Random Draft (CRD) with five repeatitions and four treatment (positive control hyperglicemic by alloxan induced without giving an Aloe vera macerate, a hyperglicemic mice give a dose Aloe vera 0,70; 1,05; 1,40ml/100g BW/day) used in this study.Four months old male mice were subjected to the Aloe vera leaf gel macerate by gavage for 30 days after 30 days acclimatization. On day 31 miceâs blood colected by injured the tail, and 1,5 Âµl blood sample was measured by Cholesterol-meter to get a concentration of cholesterol in miceâs blood. The results, show all ofAloe vera leaf gel macerate doses significantly lowering the concentration of blood cholesterol level. The Â most effective dose was Aloe vera 1,05 ml/100g BW/day which get the best decrease concentration on blood cholesterol level (164,6Â±28,5 mg/dl) in hyperglicemic mice. Aloe vera macerate can decrease blood cholesterol level because it contain the active substance such as flavonoid, fiber, unsaturated fatty acid and Vitamin A,B E. Based on these results we can conclude that the Aloe vera leaf gel macerate can be used to decrease concentration of blood cholesterol level in hyperglicemic mice.But then in the aplication of Aloe vera macerat as antihypercholesterolemic the dose and time should be pay attention more because in the long term use with high dose, Aloe vera macerate can cause a contra affect such a hypocholestrolemia.Â Â Keywords: Aloe vera, Cholesterol, hyperglicemia, mice (Mus musculus), Alloxan